2004
DOI: 10.1093/alcalc/agh031
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Carbohydrate-Deficient Transferrin in the Detection of Excessive Alcohol Consumption: A Systematic Review

Abstract: The validity of CDT as a diagnostic tool is still questionable. If the higher values for sensitivity that some studies report can be confirmed by others it is a useful diagnostic tool in unselected populations. However, more methodologically sound, comparable studies need to be performed before firm conclusions can be drawn.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(28 citation statements)
references
References 56 publications
1
25
0
2
Order By: Relevance
“…In 2000, Scouller et al (3 ) reviewed test-performance data and potential causes of variation and conducted a metaanalysis that showed that commonly used methods produced diagnostic odds ratios of approximately 12, corresponding to a 40% sensitivity at a 95% specificity, but with wide confidence intervals. Since that time, additional reports and reviews have described similarly intermediate estimates of test performance (7)(8)(9)(10)(11)(12).…”
Section: © 2008 American Association For Clinical Chemistrymentioning
confidence: 99%
“…In 2000, Scouller et al (3 ) reviewed test-performance data and potential causes of variation and conducted a metaanalysis that showed that commonly used methods produced diagnostic odds ratios of approximately 12, corresponding to a 40% sensitivity at a 95% specificity, but with wide confidence intervals. Since that time, additional reports and reviews have described similarly intermediate estimates of test performance (7)(8)(9)(10)(11)(12).…”
Section: © 2008 American Association For Clinical Chemistrymentioning
confidence: 99%
“…While self-reported data obtained by questionnaires may underestimate alcohol intake, laboratory measures provide more objective data related to ethanol metabolism. Blood tests traditionally used in the workup of alcoholism, such as liver enzyme tests (ALT, AST, GGT) and MCV, do reflect excessive, prolonged alcohol consumption but have imperfect sensitivity and specificity [22,23]. The percentage of CDT isoforms relative to the amount of total transferrin in the serum is currently considered the most sensitive and specific indicator of chronic alcohol intake [22,24].…”
Section: Discussionmentioning
confidence: 99%
“…The situation is similar with MCV, whose sensitivity and specificity are lower in relation to other alcoholism biomarkers, because its values may also be increased in liver damage, vitamin B12 and folic acid, deficiency, hematological diseases, reticulocytosis, hypothyroidism, etc. (16).…”
Section: Discussionmentioning
confidence: 99%